Experimental investigation on storage stability and phase separation behaviour of polymer-modified bitumen. Issue Volume 19:Issued 9(2018) (2nd September 2018) - Zhu, Jiqing; Lu, Xiaohu; Kringos, Niki
Abstract: Storage stability and phase separation behaviour of four styrene-butadiene-styrene (SBS) polymer-modified bitumen (PMB) binders are investigated by conventional binder tests and fluorescence microscopy in this paper. Since no separation happened in the stable PMBs, research focus was placed on capturing and analysing the phase separation process in the unstable PMBs. A phase inversion phenomenon was observed in one unstable PMB during the phase separation, showing the possible viscoelastic effects. Furthermore, it is indicated that criteria only based on compositional parameters can give misleading predictions of PMB storage stability. New criteria still need to be defined. The potential approaches to PMB phase behaviour prediction are reviewed and exploratively discussed in the context of the four investigated PMBs. This leads to a further discussion on the possibility of having a thermodynamic approach to PMB phase behaviour prediction by looking into the free energy of PMB. The Flory–Huggins theory provides a way to do this, upon the consideration of PMB as a pseudo-binary blend and some made assumptions. Free energy curves have the strength of giving more information like the equilibrium phase composition. In addition, some more aspects should be also considered for PMB phase behaviour prediction towards an applicable criterion.